A Model to Measure the Service Quality of Pharmaceutical Wholesalers - Christo A Bisschoff; Heinrich C Barnard (Journal of Economics and Behavioral Studies, 2019)
The study constituters a model to measure the service quality of pharmaceutical wholesalers in South Africa. Several pharmaceutical wholesalers distribute medical supplies throughout South Africa in a very regulated and competitive market where high service quality levels are anticipated. In this price-undifferentiated market, service quality can have a significant impact on the competitiveness of a pharmaceutical wholesaler. As a result, the primary objective was to develop a model to measure the service quality levels of large pharmaceutical wholesalers. The literature study compiled an industry profile of the South African pharmaceutical market, analysed service quality and then proposed an adapted SERVQUAL model to measure the service quality. A review of the literature also highlighted the general structure of the pharmaceutical industry and the regulatory framework in the supply of pharmaceutical products. The literature study also focuses specifically on the role and function of the pharmaceutical wholesaler in the supply chain. Data was collected from clients of a pharmaceutical wholesaler using to record the service expectations and perceptions on a seven-point Likert scale. Some 385 of the 4468 clients completed and returned the industry-adapted SERVQUAL survey questionnaires on the electronic platform Google Forms (signifying an 8.6% response rate). The results showed that the data were reliable with a Cronbach alpha coefficient higher than 0.70. The results also show that in five, the service dimensions gap where perceptions and expectations are measured had negative gaps. This means that the clients expected better service quality than what they received. The service dimension Assurance showed the largest gap, while Tangibility had the smallest gap. However, none of these gaps was practically significant. Further analysis using exploratory factor analysis identified three underlying service quality variables, namely Positive employee actions, Business process management and Marketing channels. These factors explained a favourable cumulative variance of 67.7%. The study finally proposes a model to measure service quality in the pharmaceutical wholesale industry.